Effect of Temperature, pH and Salt on Fluorescent Quality of Water Extractable Organic Matter in Black Soil - Ming-tang LI; Lan-po ZHAO; Jin-jing ZHANG (Journal of Integrative Agriculture, 2013)
Water erosion is the major reason for the loss of soil organic carbon in the Northeast China, which leads to the soil quality deterioration and adjacent water pollution. In this study, the effect of extraction temperature, pH value, and salt on the water extractable organic matter (WEOM) was determined by means of the UV absorbance, fluorescence excitation-emission matrix, and derived fluorescence indexes. In general, the carbon content and aromaticity of WEOM increased with the increasing of extraction temperature, with the exception that there was no significant difference in the amount at 0 and 20°C. More fluorophores, especially microbially-derived organic matter were extracted at high temperature. The pH values of extractant, including 5, 7, and 10, showed no effect on the carbon amount of WEOM, whereas the aromaticity and microbially-derived component gradually increased with the increasing of pH values. The fluorescence intensity of humic acid-like fluorophore was stronger in neutral and alkali condition than that in acidic condition. The addition of 10 mmol L−1 CaCl2 significantly decreased the carbon amount of recovered WEOM. Moreover, it significantly decreased the aromaticity of WEOM and the quantity of fulvic acid-like and humic acid-like fluorophores, whereas increased the percentage of tyrosine-like and tryptophan-like fluorophores in the total fluorophores and the amount of microbially-derived organic matter. Generally, 10 mmol L−1 KCl showed the same influence trend, but with low influence degree.